TRANSLATING IDIOMATIC EXPRESSIONS: A LINGUISTIC PERSPECTIVE - Yusupova Nilufar Azamatjon qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article studies the issue of translating idiomatic expressions from a linguistic point of view. Idioms are one of the riches of language, and in their translation it is not enough to search for lexical or grammatical equivalents alone, but a deep understanding of the cultural context is also important. Idiomatic expressions in English and Uzbek are analyzed, and linguistic approaches used in their translation are studied. Translation problems, their causes and solutions are highlighted on the basis of practical examples. Also, the semantic and stylistic aspects of idioms specific to both languages are analyzed on a comparative basis. The work serves as a useful theoretical and practical material for students, translators and language learners studying in the fields of translation studies, linguistics and intercultural communication.